SISTEM PENDUKUNG KEPUTUSAN SELEKSI CALON KARYAWAN BERDASARKAN HASIL TES PSIKOLOGI KEPRIBADIAN MENGGUNAKAN METODE AHP (Studi Kasus Di KALIMASADA) - Arif Harjanto (IIB Darmajaya, 2014)
A company is surely careful in selecting the prospective employees which are going to be promoted as employees in the company. A mistake in selecting employees will certainly give a negative influence on the employee performance. Besides evaluating the technical competence, the company also needs to evaluate the personality of the prospective employees. Therefore, it is needed a systematic method and right selection in selecting prospective employees. This research uses Process Hierarchy Analysis (AHP) method. The system does an evaluation on psychological test of the prospective employees’ personality, assumed to include the criteria as follows: honesty, loyalty, motivation, self-confidence and adaptation or cooperation. The system then will do analysis and evaluation on the test result of the prospective employees’ personality. The result of the research is a decision support system model of prospective employee selection based on the psychological test result, so the right selection of prospective employees can determine the real employees of the company as to the position needed. Through the research it can be made a conclusion that the system is feasible to be used by the users and good to be applied.Key Words : AHP, Personality, Employees, Selection, Decision Support System.